Caring for patients with brain tumors compared to patients with non-brain tumors: Experiences and needs of informal caregivers in home care settings. Issue 2 (4th March 2018) - Heckel, Maria; Hoser, Bettina; Stiel, Stephanie
ABSTRACT: Background/Objective: Informal caregivers of patients with advanced cancer experience a challenging time, especially while caring for the patient at home. The aim of this study is to compare experiences, perceived burdens, and needs during home care of informal caregivers of brain tumor patients and informal caregivers of non-brain tumor patients. Methods: 28 informal caregivers (17 brain tumor group, 11 non-brain tumor group) participated in this study. Semi-structured interviews were conducted to gather information retrospectively. Data was analyzed using principles of thematic analysis method. Results: The results support existing evidence that the themes assessment of the situation, dealing with the situation, effects of the situation, and support by others are of importance to all informal caregivers. Caregivers in the brain tumor group put more emphasis on information and perception of the situation by others than caregivers in the non-brain tumor group. Conclusion: The emerging need for information of caregivers and the effects for caregivers of changes in the perception of the situation by others should be addressed to better support informal caregivers of brain tumor patients.